Perceptions of employees regarding the utilization of the in-house employee assistance programme model in the North West department of education - Terblanche, Lourie (University of Pretoria, 2013)
Dissertation (M.Soc.Sci (Employee Assistance Programme))--University of Pretoria, 2007.